2021
DOI: 10.2147/jhl.s288966
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Mapping the Patient Journey for Noncommunicable Diseases in Low- and Middle-Income Countries

Abstract: Noncommunicable diseases (NCDs) are responsible for 71% of all worldwide mortality each year, and have an exceptionally large impact in low- and middle-income countries (LMICs). However, there is often a lack of local data from these countries to inform practice and policy improvements. Generating locally contextualized evidence base for NCDs that can help identify gaps, aid decision-making and improve patient care in LMICs needs an innovative approach. The approach used in Mapping the Patient Journey Towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Although the idea of patient journey maps are gaining traction [ 17 19 ], there are no standard approaches to performing the steps of the mapping exercise and it has been suggested that the lack of consistent methodology may contribute to the low adoption rates in healthcare [ 36 , 37 ]. It is important that our mapping process was patient driven.…”
Section: Discussionmentioning
confidence: 99%
“…Although the idea of patient journey maps are gaining traction [ 17 19 ], there are no standard approaches to performing the steps of the mapping exercise and it has been suggested that the lack of consistent methodology may contribute to the low adoption rates in healthcare [ 36 , 37 ]. It is important that our mapping process was patient driven.…”
Section: Discussionmentioning
confidence: 99%
“…After duplicate removal, first-level screening was done by reviewer 1 based on relevance. Non-relevant records were excluded during level-2 screening by reviewer 2 based on exclusion criteria, that included age < 18 years, case reports, letter to editors, articles with no patient journey data (prevalence, awareness, screening, diagnosis, treatment, adherence, and control), written in a non-English language, articles with non-representative study sample or study from other than Brazil region [ 18 ]. Also, this review excluded studies with specific groups of patients (elderly, pregnant women, co-morbidities).…”
Section: Methodsmentioning
confidence: 99%
“…The MAPS methodology followed in our review has been described in detail elsewhere. [ 24 25 ] Preliminary literature search for LBP with a neuropathic component in Saudi Arabia yielded only a few articles. Due to the paucity of data, a separate review article on LBP with a neuropathic component was deemed unwarranted.…”
Section: Methodsmentioning
confidence: 99%
“…[ 24 ] Consequently, the Mapping the Patient Journey Towards Actionable Beyond the Pill Solutions (MAPS) initiative has been conceptualized by Upjohn– A legacy of Pfizer Research Development and Medical that helps in managing diseases through patient-centric and locally relevant solutions. [ 25 ] Quantitative mapping of available evidence and identification of data gaps in terms of disease prevalence and patient management stages would enable the government and health-care authorities to implement relevant health-care policies, fund and prioritize specific research, and sponsor patient awareness programs in Saudi Arabia. This can be achieved through generation of evidence maps that involves evidence synthesis through a systematic search of a large field and identification of gaps in available data and/or future research needs.…”
Section: Introductionmentioning
confidence: 99%